the Importance of an early exercise and nutrition intervention among RENAL TRANSPLANT RECIPIENTS - Andrea Mahrova; Klara Svagrova; Vaclav Bunc; Milena Stollova; Vladimir Teplan (The Korean Society of Nephrology, 2012)
Typical long-term inactivity due to the dialysis, necessarily leads to a decline of the recipient's fitness level. In our study we assessed the impact of regular exercise and nutrition intervention on physical fitness and the quality of life (QoL) in the first year after kidney transplantation (Tx). Group of patients: (M/F, 11/10, age 59.1±10.8 yrs/ 57.0±8.4 yrs; 69.9±25.4/65.1±17.8 days post-Tx), randomized into 4 subgroups: exercise (E), exercise + nutrition (E+N), nutrition (N), control (C). For testing the physical fitness and QoL we used the "Senior Fitness Test Manual"and KDQOL-SFTM questionnaire. Exercise intervention focused mainly on the joint mobility, muscle strength, nimbleness, dynamic stability, and cardio respiratory endurance (3 times/week; 60 minutes; 6 months). Nutrition intervention included substitution with keto-amino-acides. Results were analysed with the non-parametric Wilcoxon and Kruskal-Wallis Test. Both physical fitness as well as QoL in the first year after Tx improved in all patients. Statistically significant differences in the dynamics of physical fitness were observed 1.- 4. months post Tx in four from six tests (p ≤ 0.01) and 1.-8. months post Tx in five from six tests (p ≤ 0.05). The greatest improvement in physical fitness was achieved by the E+N group followed by N, E and C groups. QoL improved in the groups E+N and N in seven of the eight dimensions, however the results were statistically insignificant. In conclusion, the combination of an exercise and nutrition intervention was the most effective and could give each patient an opportunity to achieve an optimal physical and psychological level almost equal to their original condition.